Chemically Induced Grain Boundary Migration in Alloy Systems - Tashiro, Kelvin M. (My University, 1986)
This thesis describes the phenomenon of chemically induced grain boundary migration, a process in which a grain boundary migrates in response to a chemical driving force. The migration characteristics from various binary alloy systems are documented, especially in the aluminum-zinc system where extensive measurements have been made in both static and dynamic situations. The dynamics of chemically induced grain boundary migration are also studied in conjunction with the growth of a second phase, a situation referred to as discontinuous precipitation. It is suggested that the force which is responsible for moving the boundary reveals different facets of itself for different cases. The facets of itself for different cases. The facets are extremes in the chemical force levels; one is at a low level and is suggested to be derived from coherency strains when solute penetration into the bulk is significant. The other force is a high level force and which originates from large concentration differences which exist across the boundary at low volume penetration levels. It is uncertain whether the transition between the two chemical driving force levels is continuous or discontinuous since the transition ranges are small. Elastic anisotropy is suggested to be responsible for the initiation of migration due to an unbalanced coherent strain energy present across the boundary. The migration process has been modeled macroscopically and computer simulated. At this time, current models of grain boundary structure are suggested to be inadequate to account for the coupling of a chemical force to grain boundary structural components.
Keywords: Physical Sciences and Mathematics; Physical Sciences and Mathematics